2000
DOI: 10.4039/ent132925-6
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSES OF CONOPHTHORUS SPP. (COLEOPTERA: SCOLYTIDAE) TO BEHAVIORAL CHEMICALS IN FIELD TRIALS: A TRANSCONTINENTAL PERSPECTIVE

Abstract: The Canadian Entomologist 132: 925 -937 (2000) We tested six behavioral chemicals, pityol, conophthorin, 4-allylanisole, verbenone, 2-hexenol, and a-pinene, in a series of field trials directed at six combinations of Conophthorus Hopkins -Pinus L. spp. (Pinaceae) Ait. trans-Verbenol was tested only on C . resinosae on P. resinosa. Traps baited with pityol caught more beetles than unbaited traps in nearly all of the assays, and conophthorin consistently inhibited male beetle response to pityol for all specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The name conophthorin comes from the genus Conophthorus, that includes species known to produce it with an inhibitor effect to aggregation pheromones or host kairomones, that is, Conophthorus coniperda (Birgersson et al 1995;de Groot et al, 1998, Rappaport et al, 2000 and C. resinosae Rappaport et al, 2000). In addition, there are several studies about the repellent effect of (E)-(-)-conophthorin and racemic conophthorin to pheromone baited traps in bark beetles species that are not known to produce it, as seen in Xylosandrus germanus (Kohnle et al 1992), Dendroctonus ponderosae (Huber et al, 1999), D. pseudotsugae (Huber et al, 1999(Huber et al, , 2000(Huber et al, , 2001, Dryocoetes confusus (Huber et al, 2000) Pityophthorus setosus (Dallara et al, 2000), C. cornicolens and C. teocotum (Rappaport et al 2000), I. pini (Huber et al, 2000(Huber et al, , 2001, I. duplicatus , I. sexdentatus (in France) (Jactel et al, 2001) and I. typographus (Zhang & Schlyter, 2003). In spite of this fact, there are reports referring to conophthorin as attractant as well, according to results observed in I. mexicanus, Lasconotus pertenuis (Coleoptera: Colydiidae) and P. carmeli (Dallara et al 2000) and in Epuraea thoracica (Coleoptera: Nitidulidae) (Kohnle et al, 1992).…”
Section: The Six-toothed Bark Beetle Ips Sexdentatus (Börner) (Fig 3)mentioning
confidence: 99%
“…The name conophthorin comes from the genus Conophthorus, that includes species known to produce it with an inhibitor effect to aggregation pheromones or host kairomones, that is, Conophthorus coniperda (Birgersson et al 1995;de Groot et al, 1998, Rappaport et al, 2000 and C. resinosae Rappaport et al, 2000). In addition, there are several studies about the repellent effect of (E)-(-)-conophthorin and racemic conophthorin to pheromone baited traps in bark beetles species that are not known to produce it, as seen in Xylosandrus germanus (Kohnle et al 1992), Dendroctonus ponderosae (Huber et al, 1999), D. pseudotsugae (Huber et al, 1999(Huber et al, , 2000(Huber et al, , 2001, Dryocoetes confusus (Huber et al, 2000) Pityophthorus setosus (Dallara et al, 2000), C. cornicolens and C. teocotum (Rappaport et al 2000), I. pini (Huber et al, 2000(Huber et al, , 2001, I. duplicatus , I. sexdentatus (in France) (Jactel et al, 2001) and I. typographus (Zhang & Schlyter, 2003). In spite of this fact, there are reports referring to conophthorin as attractant as well, according to results observed in I. mexicanus, Lasconotus pertenuis (Coleoptera: Colydiidae) and P. carmeli (Dallara et al 2000) and in Epuraea thoracica (Coleoptera: Nitidulidae) (Kohnle et al, 1992).…”
Section: The Six-toothed Bark Beetle Ips Sexdentatus (Börner) (Fig 3)mentioning
confidence: 99%
“…At higher concentrations, it served to balance the sex ratio of attacking beetles (Renwick andVité 1969, Payne et al 1978), whereas very high amounts inhibited attacks by both sexes. Verbenone synergized the attractiveness of pityol to Conophthorus ponderosae Hopkins at some release rates (Rappaport et al 2000). Verbenone also interrupted the attraction of the bark beetles D. ponderosae, D. brevicomis, Ips latidens, and Ips pini to their aggregation pheromones in a dose-dependent fashion (Paine andHanlon 1991, Miller et al 1995).…”
mentioning
confidence: 94%
“…1995; Dallara et al. 2000; de Groot and DeBarr 2000; Rappaport et al. 2000) and other xylophagous insects (Morewood et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, trans-conophthorin has also been isolated in aerations, and from the hindguts of males, of the closely related species Conophthorus coniperda (Schwarz 1895) and it was named after this genus (Birgersson et al 1995). Its biological activity in bark beetles (Kohnle et al 1992;Birgersson et al 1995;Pierce et al 1995;Dallara et al 2000;de Groot and DeBarr 2000;Rappaport et al 2000) and other xylophagous insects (Morewood et al 2003) has been widely reported. In almost all cases, ())-trans-conophthorin acts as a repellent or disruptant, with the exception of the twig beetle Pityophthorus carmeli Swaine 1918.…”
Section: Introductionmentioning
confidence: 99%